The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2009
DOI: 10.1159/000207444
|View full text |Cite
|
Sign up to set email alerts
|

Pre-Stroke Use of Antihypertensives, Antiplatelets, or Statins and Early Ischemic Stroke Outcomes

Abstract: Background: The effect of pre-stroke use of antihypertensives, antiplatelets, and statins on initial severity and early outcome of ischemic stroke is uncertain. Methods: We performed a retrospective chart review of 553 consecutive acute ischemic stroke patients presenting to the Montreal General Hospital between April 1st 2002 and October 15th 2005. We defined a severe stroke as a Canadian Neurological Scale score of ≤7 and a poor early outcome as a modified Rankin Scale score of >3 at 10 days post-stroke. Res… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
19
0
1

Year Published

2009
2009
2017
2017

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(20 citation statements)
references
References 65 publications
0
19
0
1
Order By: Relevance
“…Two other studies detected an association between the use of nonthiazide antihypertensives and an increased risk of first stroke and stroke severity. 30,31 We found ␤-blocker therapy and thiazide diuretic therapy to be associated with a higher risk of recurrent stroke events; furthermore, use of nonthiazide antihypertensives was associated with a higher risk of AMI in our study (Table). Interestingly, recent work from Rothwell and colleagues based on RCT data demonstrate that a high-dose calcium channel blocker reduces systolic blood pressure variability compared with other blood pressurelowering agents, in particular ␤-blockers, and that treatment with calcium channel blockers may therefore be particularly effective in the prevention of stroke.…”
Section: Discussionmentioning
confidence: 52%
“…Two other studies detected an association between the use of nonthiazide antihypertensives and an increased risk of first stroke and stroke severity. 30,31 We found ␤-blocker therapy and thiazide diuretic therapy to be associated with a higher risk of recurrent stroke events; furthermore, use of nonthiazide antihypertensives was associated with a higher risk of AMI in our study (Table). Interestingly, recent work from Rothwell and colleagues based on RCT data demonstrate that a high-dose calcium channel blocker reduces systolic blood pressure variability compared with other blood pressurelowering agents, in particular ␤-blockers, and that treatment with calcium channel blockers may therefore be particularly effective in the prevention of stroke.…”
Section: Discussionmentioning
confidence: 52%
“…Other preexisting CVDs are present in the majority of poststroke individuals: high rates of CAD, chronic hypertension, atrial fibrillation, hyperlipidemia, metabolic syndrome, and diabetes mellitus. 41,42 Although traditionally, stroke has not been considered a CVD, vascular health appears to have important implications for recovery from stroke, with low aortic stiffness being a biomarker of vascular integrity that is associated with favorable neurological outcomes at hospital discharge. 43 There is strong evidence for a clear inverse relation between physical activity and cardiovascular health.…”
Section: August 2014mentioning
confidence: 99%
“…More recently Yu et al [44] showed that the combination of antihypertensives, antiplatelets, and statins were both associated with a favorable functional outcome at 10 days post-stroke. Angiotensin-II-decreasing agents were associated with increased initial stroke severity.…”
Section: Aspirinmentioning
confidence: 99%